Lakes restoration: analysis of terminology incorrectly used in the scientific literature - Robert Mazur (Acta Scientiarum Polonorum. Formatio Circumiectus)
Water reservoir restoration process is of a holistic nature and requires the application of many reclamation and remediation methods. The final result should be the restoration of the state of the primary aquatic environment that occurred before the adverse anthropogenic changes. The condition of many water reservoirs in the world requires taking redegradation method to restore the water quality. Water rehabilitation activities conducted by specialized companies or expert teams are colloquially called “water restoration”. The author presented the problem of incorrect naming of water restoration processes in the aspect of “water restoration” process. He pointed to selected examples of scientific and industry articles, of incorrect use of the word "reclamation" and suggested the proper naming in relation to the nature of the corrective actions taken. Commercialization of the f “water restoration” word is undoubtedly the cause of its abuse and misuse in many activities, which in the end do not meet the objectives of lake restoration.